2005
DOI: 10.1111/j.1440-1770.2005.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortalities of lesser flamingos in Kenyan Rift Valley saline lakes and the implications for sustainable management of the lakes

Abstract: Lesser flamingo populations in the Kenyan Rift Valley saline lakes respond to changes in phytoplankton species' composition and densities, behavioural needs, breeding cycles and environmental conditions. The numbers of flamingos are high when the density of blue-green algae Arthrospira fusiformis (Spirulina platensis) is high, stimulating flamingo courtship and display. The numbers decline when lake levels decline, resulting in low phytoplankton densities and a domination by toxic phytoplankton species. In Ken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 40 publications
0
32
2
Order By: Relevance
“…Our findings contradict the observations made by Githaiga (2003) and Ndetei & Muhandiki (2005) who reported on the occurrence of Microcystis in lakes Bogoria, Elmentaita and Nakuru and attributed the flamingo mass die offs in 1993, 1997, and 2001 to Microcystis toxins. The two studies did not provide any photographic documentation of the Microcystis species observed to allow for independent confirmation.…”
contrasting
confidence: 85%
See 1 more Smart Citation
“…Our findings contradict the observations made by Githaiga (2003) and Ndetei & Muhandiki (2005) who reported on the occurrence of Microcystis in lakes Bogoria, Elmentaita and Nakuru and attributed the flamingo mass die offs in 1993, 1997, and 2001 to Microcystis toxins. The two studies did not provide any photographic documentation of the Microcystis species observed to allow for independent confirmation.…”
contrasting
confidence: 85%
“…Presently, the food chains of these lakes is the focus of intense scientific discussion as the lakes host toxic cyanobacteria, which when consumed by Lesser Flamingos, weakens the birds, and therefore makes them susceptible to attacks by infective diseases (Motelin et al, 2000;Codd et al, 2003;Krienitz et al, 2003;Ballot et al, 2004Ballot et al, , 2005Koenig, 2006;Kotut et al, 2006;Lugomela et al, 2006;. Recently, high densities of Microcystis in lakes Bogoria, Elmentaita, and Nakuru were reported and related to mass die offs of Lesser Flamingos (Githaiga, 2003;Ndetei & Muhandiki, 2005;Stewart et al, 2008). For the last 10 years, we have discussed with colleagues involved in planktological research and those in wildlife protection agencies across different countries of East Africa, the possible occurrence of Microcystis in alkaline saline lakes and came to the conclusion that there is a high level of uncertainty.…”
mentioning
confidence: 94%
“…In L. Nakuru, reports indicated sudden mortalities from 1993 to 2003, with deaths going beyond 500 in 1998 (Ndetei & Muhandiki, 2005). Krienitz & Kotut (2010) reported the highest mortality of flamingos (*30,000) in L. Nakuru in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the same authors also recorded about 30,000 carcasses of Lesser Flamingos that had accumulated along the shoreline of L. Bogoria. Among the possible causes for the sudden mortalities cited were the changes in food quantity (Sileo et al, 1979;Mlingwa & Baker, 2006) and composition (Ndetei & Muhandiki, 2005;Krienitz & Kotut, 2010). Problems with food composition are mainly associated with mucilage clogging the filters in the beaks and the production of cyanobacterial toxins by some taxa of cyanobacteria, which are ingested during feeding (Vareschi, 1978;Codd et al, 2003;Krienitz et al, 2003;Krienitz & Kotut, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Such contaminations are a major cause of illness and death worldwide, particularly in developing countries (WHO, 1998;Foulds et al, 2002). Cyanobacteria are globally distributed in both fresh and marine water (Dor and Danin, 1996) and toxic cyanobacterial blooms have been reported in most parts of the world (Ochumba, 1990;WHO, 1999;Ballot et al, 2004;Ndetei and Muhandiki, 2005). Some cyanobacterial strains are harmful to animals and humans because of the toxins they produce, known as cyanotoxins.…”
Section: Introductionmentioning
confidence: 99%